A beam‐formed leaky‐wave antenna array with power‐recycling feeding network. Issue 10 (29th June 2022) - Zhang, Yulu; Wang, Junhong; Geng, Yunjie
Abstract: A substrate integrated waveguide leaky‐wave antenna array using power‐recycling feeding network to achieve beamforming radiation pattern is investigated in this article. The antenna array consists of three elements represented by An1, An2, and An3 on two kinds of radiation mechanism. An1 and An2 are working on the ‐1th spatial harmonic mode with broadside and backward radiation directions, respectively, and An3 is working on the fundamental wave mode with forward radiation direction. The open‐stopband due to broadside radiation design in An1 is suppressed by arranging two similar slots in one radiation unit. By using power‐recycling feeding network, the traveling wave directions in An2 and An3 are opposite, which partially compensates the opposite radiation directions of these two elements. Therefore, by adjusting the sizes of radiation slots appropriately, the proposed antenna array can achieve a cosecant–distribution radiation pattern within the range from 0° to 50°.